Dexmedetomidine attenuates lipopolysaccharide-induced acute liver injury in rats by inhibiting caveolin-1 downstream signaling pathway. Issue 3 (26th March 2021) - Tong, Fei; Shen, Wenchao; Song, Pengtao; Song, Jiafeng; Hu, Yonghe; Liu, Feifan; Meng, Zhipeng; Liu, Jing
Abstract: Objective: The aim of the present study is to investigate the anti-injury and anti-inflammatory effects of dexmedetomidine (Dex) in acute liver injury induced by lipopolysaccharide (LPS) in Sprague–Dawley rats and its possible mechanism. Methods: The acute liver injury model of male rats was established by injecting LPS into tail vein. The mean arterial pressure (MAP) of rats was recorded at 0–7 h, and lactic acid was detected at different time points. Wet/dry weight ratio (W/D) was calculated. Pathological changes of rat liver were observed by HE staining. ALT and AST levels in serum were detected. The activities of myeloperoxidase (MPO) and superoxide dismutase (SOD) in liver tissue homogenate and the levels of IL-1β and IL-18 in serum were detected by ELISA. Protein levels of Caveolin-1 (Cav-1), TLR-4 and NLRP3 in liver tissue were tested by immunohistochemistry method. The expression of Cav-1, TLR-4 and NLRP3 mRNA in liver tissue was detected by quantitative polymerase chain reaction (qPCR) to explore its related mechanism. Results: Compared with NS group, serum lactic acid, W/D of liver tissue, MPO, SOD, IL-1β and IL-18 were significantly increased and MAP decreased significantly in LPS group and D+L group. However, compared with NS group, D group showed no significant difference in various indicators. Compared with LPS group, MPO, SOD, IL-1β and IL-18 were significantly decreased and MAP was significantly increased in D+L group. D+L group could significantly increase the level of Cav-1 protein and decrease the level of TLR-4 and NLRP3 protein in liver tissue caused by sepsis. The expression of Cav-1 mRNA was significantly up-regulated and the expression of TLR-4 and NLRP3 mRNA was inhibited in D+L group. Conclusion: Dex pretreatment protects against LPS-induced actue liver injury via inhibiting the activation of the NLRP3 signaling pathway by up-regulating the expression of Cav-1 by sepsis.